Stereotip Terhadap Perempuan Melalui Karakter Jeng Yah Dalam Series Gadis Kretek - Noni Octavia; Ningsi Demanto; Septia Intan Nurzannah (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
Films and other cultural media not only present stories, but also messages and values conveyed through characters, plots, and themes including about gender stereotypes. The topic still exists, women are portrayed as passive figures, focusing only on domestic roles, while men are depicted as having more dominant roles. It triggers injustice and discrimination against women. Gender disparities are rooted in gender stereotypes towards men and women. The research focuses on the stereotypical portrayal of women through the character Jeng Yah in five episodes of the Cretaceous Girls series on Netflix. By using qualitative methods with critical discourse analysis of Sara Mills to analyze gender representation in the series in question. Some of the main points that indicate gender stereotypes against women are: women can only do certain jobs deemed appropriate to them, women do not have full control over their own lives, including important decisions that affect their freedom/future, women are often regarded as bearing "devotion", and are identified with weakness. The series shows how gender stereotypes are still inherent in societies even coming from their own families, and how they can limit women in various aspects of life. This research can help raise awareness about gender stereotypes and promote gender equality.